Federalism and the constitution of Canada - Smith, David E., 1936-2023 (University of Toronto Press, 2010)
In Federalism and the Constitution of Canada, award-winning author David E. Smith examines a series of royal commission and task force inquiries, a succession of federal-provincial conferences, and the competing and controversial terms of the Constitution Act of 1982 in order to evaluate both the popular and governmental understanding of federalism. In the process, Smith uncovers the reasons constitutional agreement has historically proved difficult to reach and argues that Canadian federalism 'in practice' has been more successful at accommodating foundational change than may be immediately apparent."--Pub. desc.